Asian cities globalization, urbanization and nation-building - McKinnon, Malcolm (Nordic Institute of Asian Studies monograph series, 2011)
Challenges Western paradigms of urban growth with a fresh look at cities in developing Asia. This book questions the status accorded to globalization in explaining contemporary Asian cities, arguing instead that they are being transformed by three major forces - urbanization and nation-building as well as globalization